2020
DOI: 10.1111/spol.12619
|View full text |Cite
|
Sign up to set email alerts
|

Decent work for sustainable development inpost‐crisisNepal: Social policy challenges and a way forward

Abstract: Although the Decent Work agenda has received significant attention in the context of sustainable development, the formulation and implementation of appropriate social policies in developing countries remain an underexplored subject. This article responds to this gap and traces country-specific Decent Work related policies and programs in Nepal-which is recovering from two major crises: a decade-long armed conflict that ended in 2006 as well as the 2015 earthquake. Drawing on Critical Policy Analysis framework,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(7 citation statements)
references
References 41 publications
0
6
0
1
Order By: Relevance
“…It is assumed that some factors such as the developmental status of countries may affect the effects of promoting decent work. For example, in developing countries where working conditions are usually jeopardized by the deprivation of social and economic resources, how to position the goal of promoting decent work remains a controversial topic (Singh, 2017 ; Dhakal and Burgess, 2021 ). In China, the goal of achieving decent work is still at an early stage and the majority of the public are not able to associate the decent work notion with their present or future work (Cooke et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is assumed that some factors such as the developmental status of countries may affect the effects of promoting decent work. For example, in developing countries where working conditions are usually jeopardized by the deprivation of social and economic resources, how to position the goal of promoting decent work remains a controversial topic (Singh, 2017 ; Dhakal and Burgess, 2021 ). In China, the goal of achieving decent work is still at an early stage and the majority of the public are not able to associate the decent work notion with their present or future work (Cooke et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Research by Dhakal and Burgess (2020) showed that the implementation of the social aspect of sustainable development (eg. Goal 8) in ensuring decent working conditions for employees is determined by the level of development of the country.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the context of an ongoing COVD-19 pandemic, various aging-related policy issues are likely to emerge as new research priorities in the immediate future (Dhakal et al 2021 ; Solanki et al, 2021 ). As the primary purpose of social policy innovation is to improve human wellbeing, especially the welfare of those disadvantaged, marginalised, and vulnerable (see Dhakal & Burgess, 2021 ), future studies should consider these observations to inform evidence-based policy discussions (see Head 2016 ) and guide future research directions.…”
Section: Conclusion Implications and Limitationsmentioning
confidence: 99%